Satisfaction in the Soul: Common Factors Theory Applied to Traditional Healers in Rural Nepal. (29th June 2020) - Pham, Tony V.; Koirala, Rishav; Kohrt, Brandon A.
Abstract: To explore the relationship between traditional healers and conventional psychotherapy, we conducted a combined ethnographic study and structured observational rating of healers in the middle hill region of central Nepal. We conducted in‐depth interviews and ethnographic observations of healing with 84 participants comprising 29 traditional healers and 55 other community members. Overall, our observations and participant responses yielded a range of interventions that improved health through belief, satisfaction in the soul, social support, transference, and symbolic narration. The findings from our overall ethnography suggest that healers offer a platform for their patients to accept a disease state, cope with it, and to experience palliation of distress. We additionally focused on one participant who saw multiple healers for a case study, during which we rated healing behavior using an observational measure of empathy, emotional validation, and therapeutic alliance. Using this measure, healers who were perceived as successful, scored high on alliance, empathy, promoting expectations of recovery, and use of cultural models of distress. The results of our structured observation suggest healers draw upon processes also observed in psychotherapy. Further research is needed to explore if these practices can be generalized to healers in other parts of Nepal and other settings. सार: